2002
DOI: 10.1002/eqe.120
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical hysteretic model for elastomeric isolation bearings

Abstract: SUMMARYAn analytical model for high damping elastomeric isolation bearings is presented in this paper. The model is used to describe mathematically the damping force and restoring force of the rubber material and bearing. Ten parameters to be identiÿed from cyclic loading tests are included in the model. The sensitivity of the ten parameters in a ecting the model is examined. These ten parameters are functions of a number of in uence factors on the elastomer such as the rubber compound, Mullins e ect, scraggin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 8 publications
1
43
0
Order By: Relevance
“…Thus, the method proposed by Hwang et al [12], Yoshida et al [13] and Hwang and Ku [14] and accepted by technical codes [16][17][18] provides results that are close to the method proposed by the authors for the stationary response. The only significant approximation introduced is due to the difference of periods between the nonlinear system and the equivalent linear system.…”
Section: Approximate Evaluation Of Equivalent Parameterssupporting
confidence: 73%
See 1 more Smart Citation
“…Thus, the method proposed by Hwang et al [12], Yoshida et al [13] and Hwang and Ku [14] and accepted by technical codes [16][17][18] provides results that are close to the method proposed by the authors for the stationary response. The only significant approximation introduced is due to the difference of periods between the nonlinear system and the equivalent linear system.…”
Section: Approximate Evaluation Of Equivalent Parameterssupporting
confidence: 73%
“…Papers that aim at describing the seismic behaviour of HDR devices usually propose constitutive laws based on simple models modified to take into account the strongly nonlinear strain dependence and the strain rate dependence [10][11][12]. Few works have attempted to model even the process-dependent behaviour [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the works of Dall'Asta and Ragni [18]; Hwang et al [19] and Tsai et al [20] can be reported. They studied the mechanical behavior of high damping rubber dissipating devices by conducting different experiments such as sinusoidal loading tests at different frequencies, simple cyclic shear tests at different strain-rates along with relaxation tests.…”
Section: Introductionmentioning
confidence: 94%
“…The general mechanical behavior of laminated rubber bearings mainly concerns with nonlinear rate-dependent hysteretic property [18,19] in addition to other inelastic behavior like Mullin's softening effect [30] and relaxation behavior [31]. All these characteristic behaviors generally originate from the molecular structures of the strength elements of rubber materials used in manufacturing of the bearings.…”
Section: Introductionmentioning
confidence: 99%
“…For representation of variation of isolator's stiffness at repeating cycles due to scragging [16][17][18], the following dependence is accepted in Simulink models:…”
Section: Models Of Seismic Elastomeric Isolatorsmentioning
confidence: 99%